2007
DOI: 10.1016/j.jocn.2006.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic arteriovenous fistula of the superficial temporal artery

Abstract: Arteriovenous fistulae of the superficial temporal artery are rare, and their principal cause is traumas. Complications include pulsatile mass, headache, hemorrhage and deformities that compromise esthetics. Treatment can be performed using conventional surgery or endovascular methods. The authors describe a case of a 44-year-old male patient who developed a large pulsating mass, extending from the preauricular region to the right parietotemporal and frontal regions after a motorcycle accident. The treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 20 publications
(7 reference statements)
0
85
1
Order By: Relevance
“…However, Luessenhop found that the risk of recurrence after embolization was high as this method could not deal with all the pericranial vessels (22). Moreover, there are many other complications after embolization such as the pain at the fistula site, tenderness and hyperemia over the skin, necrosis over the lesion, escape of the embolic material to the circulation, and permanent patchy hair loss that may not improve and lead to cosmetic problems (1, 15,17,21). Therefore, subsequent surgical removal of the embolic material is necessary in many cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Luessenhop found that the risk of recurrence after embolization was high as this method could not deal with all the pericranial vessels (22). Moreover, there are many other complications after embolization such as the pain at the fistula site, tenderness and hyperemia over the skin, necrosis over the lesion, escape of the embolic material to the circulation, and permanent patchy hair loss that may not improve and lead to cosmetic problems (1, 15,17,21). Therefore, subsequent surgical removal of the embolic material is necessary in many cases.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid torrential hemorrhage, we dissected the huge dilated vessels patiently and carefully as we were cutting the scalp. To ensure a complete resection, both the ligation of proximal feeding arteries (21) and the resection of the draining veins were very important. During surgery, we also found numerous small tortuous draining veins and feeding arteries in the subcutaneous layer of the scalp and these were not detected by preoperative CTA or DSA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They generally develop in the trauma background and in patients over 30 years old. Spontaneous AVM of the scalp may present at birth; however, in most patients, it is asymptomatic until adulthood [3,[8][9]. Trauma, pregnancy, or hormonal changes cause deterioration of the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This may occur following a variety of insults, including: Car accidents, diving accidents, penetrating injuries from assaults with sharp objects, and iatrogenic etiologies, such as temporomandibular joint arthroscopy and punch-graft hair transplantation [1]. The literature related to scalp AVF following hair transplantation is limited primarily to single case reports [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%